Crystalline bis(η5-cyclopentadienyl)bis(benzoato/carboxylato)titanium(IV) precursordirected route to functional titanium dioxide nanomaterials - Basu Baul, Tushar S.; Manne, Rajesh; Tiekink, Edward R. T. * (Taylor & Francis, 2018)
Five titanocene(IV) carboxylates of the general formula Cp2Ti(O2CR)2 viz., [Ti(η5-C5H5)2(O2CC6H5-4-CH3)2] (1), [Ti(η5 -C5H5)2(O2CC4H3-2-O)2] (2), [Ti(η5-C5H5)2(O2CC4H3-3-O)2] (3), [Ti(η5-C5H5)2(O2CC(CH3)3)2] (4) and [Ti(η5-C5H5)2(O2C(CH)C(CH3)3)2] (5) have been synthesized. All the titanocene(IV) carboxylates have been characterized by IR, 1H and 13C NMR spectroscopic techniques, and the crystal and molecular structures of 1-5 have been determined by single crystal X-ray crystallography. The structures present similar features with monodentate carboxylate ligands and tetrahedral Ti centres, assuming the each Cp ring occupies one position only. The differences in the structures relate primarily to the relative orientations of the carboxylate ligands. In the molecular packing, non-conventional Cp-C–H …O(carbonyl) hydrogen bonds are observed in each case and lead to supramolecular chains in each of 1, 4 and 5. In 2, the 2-furyl-O atoms also participate in C–H …O interactions leading to a two-dimensional array. Finally, in 3, a two-dimensional array arises as a result of Cp-C–H …O(carbonyl) and 3-furyl-C–H …O(carbonyl) interactions. As representative example, compound 3 was used as starting material for the synthesis of TiO2 nanoparticles.